1999
DOI: 10.1046/j.1460-9568.1999.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural trait of reactivity to novelty is related to hippocampal neurogenesis

Abstract: The hippocampal formation is one of the brain areas where neurogenesis persists during adulthood, with new neurons being continuously added to the population of dentate granule cells. However, the functional implications of this neurogenesis are unknown. On the other hand, the hippocampal formation is particularly concerned with the detection of novelty, and there are indications that dentate granule cells play a significant role in this function. Recently, the existence of inter-individual differences in beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
2
2

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 60 publications
5
78
2
2
Order By: Relevance
“…Stressful events and the concomitant release of corticosterone are known to inhibit cell proliferation. [35][36][37][38] However, our experiments were specifically designed to control for the potential effects of stress. Animals were habituated to the pool before training and two control groups were used: Unmanipulated animals that were not exposed to the pool and Yoked animals that were exposed to the pool without the platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stressful events and the concomitant release of corticosterone are known to inhibit cell proliferation. [35][36][37][38] However, our experiments were specifically designed to control for the potential effects of stress. Animals were habituated to the pool before training and two control groups were used: Unmanipulated animals that were not exposed to the pool and Yoked animals that were exposed to the pool without the platform.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects with the five highest and lowest BrdU-IR cell counts 35,36 were compared for their performance in the water-maze. As shown in Figure 5, animals with the lowest number of BrdU-IR cells had a better performance in the water-maze than animals with the highest number of BrdU-IR cells (Group effect, F 1,8 ¼13.07, P¼0.007).…”
Section: Late Phase Of Learning Decreases the Number Of Cells Born Dumentioning
confidence: 99%
“…Regardless, these unique properties of adult born, immature neurons may qualify them for functions that mature developmentally generated cells are less suited to accomplish (Gould et al, 1999b). For example, it has been suggested that new cells born in adulthood could be used to detect or process novel stimuli (Kempermann, 2002;Shors, 2004;Becker, 2005), a function that has been ascribed to the hippocampus (Lemaire et al, 1999;Nyberg, 2005).…”
Section: How Might New Neurons Participate In Learning and Memory?mentioning
confidence: 99%
“…The possibility that more new neurons could improve learning has been supported by animal studies. In rats, increased DG neurogenesis occurs following hippocampal-dependent associative learning (Gould et al, 1999), especially in relatively demanding learning tasks (Shors et al, 2001) or after exposure to novel contexts (Lemaire et al, 1999). In mouse strains showing different baseline rates of hippocampal neurogenesis, higher-rate strains showed steeper spatial learning curves (Kempermann and Gage, 2002).…”
Section: Effects Of Increasing Proportions Of Neurons Undergoing Turnmentioning
confidence: 99%